The role of G protein-coupled receptor in neutrophil dysfunction during sepsis-induced acute respiratory distress syndrome - Wang, Yi; Zhu, Cheng-long; Li, Peng; Liu, Qiang; Li, Hui-ru; Yu, Chang-meng; Deng, Xiao-ming; Wang, Jia-feng (Frontiers in Immunology, 2023)
Sepsis is defined as a life-threatening dysfunction due to a dysregulated host response to infection. It is a common and complex syndrome and is the leading cause of death in intensive care units. The lungs are most vulnerable to the challenge of sepsis, and the incidence of respiratory dysfunction has been reported to be up to 70%, in which neutrophils play a major role. Neutrophils are the first line of defense against infection, and they are regarded as the most responsive cells in sepsis. Normally, neutrophils recognize chemokines including the bacterial product N-formyl-methionyl-leucyl-phenylalanine (fMLP), complement 5a (C5a), and lipid molecules Leukotriene B4 (LTB4) and C-X-C motif chemokine ligand 8 (CXCL8), and enter the site of infection through mobilization, rolling, adhesion, migration, and chemotaxis. However, numerous studies have confirmed that despite the high levels of chemokines in septic patients and mice at the site of infection, the neutrophils cannot migrate to the proper target location, but instead they accumulate in the lungs, releasing histones, DNA, and proteases that mediate tissue damage and induce acute respiratory distress syndrome (ARDS). This is closely related to impaired neutrophil migration in sepsis, but the mechanism involved is still unclear. Many studies have shown that chemokine receptor dysregulation is an important cause of impaired neutrophil migration, and the vast majority of these chemokine receptors belong to the G protein-coupled receptors (GPCRs). In this review, we summarize the signaling pathways by which neutrophil GPCR regulates chemotaxis and the mechanisms by which abnormal GPCR function in sepsis leads to impaired neutrophil chemotaxis, which can further cause ARDS. Several potential targets for intervention are proposed to improve neutrophil chemotaxis, and we hope that this review may provide insights for clinical practitioners.